Anti-Ageism Social Actions: Lights and Shadows - Macarena Sánchez-Izquierdo; Rodrigo García-Sánchez; Rocío Fernández-Ballesteros (Land, 2022)
Ageism refers to the stereotypes, prejudices and discrimination towards others or oneself due to age, and it is the most prevalent type of social disadvantage, even more so than those due to gender and race, with negative effects worldwide. Ageism is an evidently real social problem that needs to be addressed and fought. Our study has two main objectives: firstly, to study to what extent programmes, projects or actions have been developed to combat ageism around the world; and secondly, to what extent they have been evaluated via the positive outcomes registered by the participants. Two different information sources were used: (a) a literature review of ageism programmes or interventions; and (b) an online questionnaire sent to international and national institutions surveying their policies or programmes against ageism. Our results show a relatively high number of actions combating ageism but a lack of a systematic evaluation of the outcomes of those actions. In conclusion, first, it is necessary to develop programmes and actions combating ageism, and the evaluation of these programmes is urgently needed in order to identify strategies that truly and effectively tackle ageism. There is a need to urge institutions to perform external evaluations of their anti-ageism social policies and to encourage scientists to conduct randomized and controlled studies.